Contexts of vulnerabilities experienced by adolescents: challenges to public policies - Aline dos Santos Gasparetto; Tassia de Arruda Bonfim; Elen Ferraz Teston; Priscila Maria Marcheti; Sueli Aparecida Frari Galera; Bianca Cristina Ciccone Giacon-Arruda
ABSTRACT Objectives: to understand the context of vulnerability experienced by adolescents from the perspective of health professionals from the Family Health Strategy. Methods: a descriptive-exploratory qualitative study developed with 80 Family Health Strategy professionals in the Midwest region of Brazil. Data collection was developed from July to September 2018 through a focus group, and submitted to Thematic Analysis. Results: it was understood that the vulnerability experienced by adolescents is not an exposure to something isolated, but is linked to risk and protection factors, socioeconomic and cultural contexts, public and health policies. Final Considerations: there are still gaps in public policies for this population, which impacts on the access and development of promotion actions by health professionals.